Local Institutions, Poverty, and Household Welfare in Bolivia - Grootaert, Christiaan; Narayan, Deepa (World Bank, Washington, DC, 2014)
The authors empirically estimate the impact of social capital on household welfare in Bolivia--where they found 67 different types of local associations. They focus on household memberships in local associations as being especially relevant to daily decisions that affect household welfare and consumption. On average, households belong to 1.4 groups and associations: 62 percent belong to agrarian syndicates, 16 percent to production groups, 13 percent to social service groups, and 10 percent to education and health groups. Smaller numbers belong to religious and government groups. Agrarian syndicates, created by government decree in 1952, are now viewed mainly as community-initiated institutions to manage conmunal resources. They have been registered as legal entities to work closely with municipalities to represent the interests and priorities of local people in municipal decisionmaking. The effects of social capital operate through (at least) three mechanisms: sharing of information among association members; the reduction of opportunistic behavior; and better collective decisionmaking. The effect of social capital on household welfare was found to be 2.5 times that of human capital. Increasing the average educational endowment of each adult in the household by one year (about a 2.5-percent increase) would increase per capita household spending 4.2 percent; a similar increase in the social capital endowment would increase spending 9 to 10.5 percent. They measured social capital along six dimensions: density of memberships, internal heterogeneity of associations (by gender, age, education, religion, etc.), meeting attendance, active participation in decisionmaking, payment of dues (in cash and in kind), and community orientation. The strongest effect came from number of memberships. Active membership in an agrarian syndicate is associated with an average 11.5 percent increase in household spending. Membership in another local association is associated with a 5.3-percent higher spending level. Empirical results partly confirm the hypothesis that social capital provides long-term benefits such as better access to credit and a higher level of trust in the community as a source of assistance in case of need.